Patient factors driving overuse of cardiac catheterisation: a qualitative study with 25 participants from two German teaching practices - Herwig, Anna (BMJ Open, 2019)
OBJECTIVES: Percutaneous coronary interventions do not provide a benefit over medical therapy for stable patients. However, an overuse of cardiac catheterisation (CC) for stable coronary artery disease (CAD) is documented in Germany and other countries. In this study, we aim to understand patient factors that foster this overuse. DESIGN: Our study is an exploratory qualitative interview study with narrative, structured interviews. The interviews were analysed using qualitative content analysis by Mayring. SETTING: The interviews were conducted in two German teaching practices. PARTICIPANTS: 24 interviews with 25 patients were conducted; 17 (68%) patients were male, the average age was 73.9 years (range 53–88 years). All patients suffered from CAD and had undergone at least one CC. Patients with known anxiety disorders were excluded from the study. RESULTS: The analysis identified six patient factors which contributed to or prevented the overuse of CC: (1) unquestioned acceptance of prescheduled appointments for procedures/convenience; (2) disinterest in and/or lack of disease-specific knowledge; (3) helplessness in situations with varying opinions on the required care; (4) fear of another cardiac event, (5) patient–physician relationship and (6) the patient’s experience that repeat interventions did not result in a change of health status or care. CONCLUSIONS: Conducted in a country with documented overuse of CC, we showed that most patients trusted their physicians’ recommendations for repeat coronary angiographies even if they were asymptomatic. Strategies to align physician adherence with guidelines and corresponding patient information are needed to prevent overuse.